Interpreting the General Letters : an exegetical handbook - Bateman, Herbert W., 1955-; Harvey, John D., 1951- (Grand Rapids, MI : Kregel Academic, 2013)
This handbook is designed as a step-by-step approach for analyzing and communicating eight letters of the New Testament: Hebrews, James, the Petrine Letters, the Johannine Letters, and Jude. Interpreting the General Letters provides important background material for these books' interpretation by exploring the types and component parts of letter writing, the importance of an amanuensis; the historical background of the Greco-Roman world, and implications of each of these factors for interpreting the general letters. --from publisher description
Includes bibliographical references
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics